1917-1967 : zemlya krest'yanam! Mir narodam! (Советский художник (Soviet Artist), 1967)
Thumbnails of historical Lenin paintings, posters, and illustrations Original title: 1917-1967 : земля крестьянам! Мир народам! PO-1144